TECHNOLOGY OF TEACHING ANALYTICAL READING OF LITERARY TEXT - Karapetyan, Igor; Gevorgyan, Ruzanna (Foreign Languages for Special Purposes, 2024)
In a philologically oriented English language course, various technologies for analytical reading of literary text are used. There are various technologies of analytical reading: technologies of fast, rational, dynamic reading, technology of developing critical thinking, technology of using various reading strategies, technology of reflective reading at different levels, technology of speech analysis, etc.. When developing and organizing each course lesson, the problem of concretizing the technology of analytical reading of a literary text arises.It is important that teachers constantly develop their methodological arsenal and study the  technologies of analytical reading. Consistent reading of foreign language fiction is a necessary and important condition for using the technologies mentioned. Besides, both teachers and students should read works of art. It is effective to present a reading list to students at the beginning of the course. Besides, it is effective when the student himself chooses from the mentioned list the minimum that he should read. It is effective when reading each literary work begins with an awareness of a clear purpose and problems of reading.To use the technology of cognitive-discourse analytical reading demands to carry out serious and consistent preparatory work. It is important in this sense, to study both linguistic and literary works in native and foreign languages.
Keywords: rational reading; dynamic reading; critical thinking; reading strategy; synthetic reading; reflective reading; cognitive-discursive technology; literary text